ANALISIS KETERLAMBATAN PENGIRIMAN PRODUK JADI DI PT TSUCHIYOSHI PROCORE INDONESIA - Vikaliana, Resista; Arizqi, Reza Miftah Nur (Jurnal Intent: Jurnal Industri dan Teknologi Terpadu, 2023)
Transportation and distribution management is a process of distributing goods by an institution to manage the distribution process in fulfilling customer needs systematically. The goal of this research is to find out what factors that might delay the shipment and to analyze the improvement steps and the shipment process in PT Tsuchiyoshi Procore Indonesia in order to help the company to decide what to do. The research method that the author uses is qualitative descriptive, by conducting interviews with informants, documentation and utilization of fishbone diagrams and pareto principles. The author succeeded in concluding the cause of the delay in the shipment process are running out of stock and low production, mostly were caused by the quality of manpower that needed to be improved and the placement of finished products in the warehouse currently did not have an appropriate method.